2019
DOI: 10.5812/iji.89636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant Staphylococcus aureus in Hospitals and Community in Duhok, Kurdistan Region of Iraq

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a serious concern of the global health sector and more recently, an escalating problem in the community. Objectives: This study was performed to investigate the incidence of MRSA in hospital staff and community students in Duhok, Kurdistan, Iraq, and make a molecular comparison between the strains based on the detection of mecA gene and Panton-Valentine Leukocidin (PVL) gene. Methods: We obtained 109 and 103 samples from the nares of hospital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
4
13
3
1
Order By: Relevance
“…In agreement with some studies results, more than 90% of the isolates were susceptible to vancomycin [1,3,[15][16][17] . Out of the 73 isolates, 32 (43.8%) were MRSA, this finding is in line with the results of the studies by Dibah et al (2014) 57 (78) [16] and Mir et al (2019) [14] in Ardabil and Zabol, respectively; however, dissimilar prevalence rates have been reported by other researchers in Iran and other countries [1,3,5,7,9,13,17,[18][19].…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with some studies results, more than 90% of the isolates were susceptible to vancomycin [1,3,[15][16][17] . Out of the 73 isolates, 32 (43.8%) were MRSA, this finding is in line with the results of the studies by Dibah et al (2014) 57 (78) [16] and Mir et al (2019) [14] in Ardabil and Zabol, respectively; however, dissimilar prevalence rates have been reported by other researchers in Iran and other countries [1,3,5,7,9,13,17,[18][19].…”
Section: Discussionsupporting
confidence: 88%
“…Numerous studies in our area have found high rates of S. aureus among general population (Rasheed and Hussein, 2020e), healthcare worker (Hussein et al, 2019) and students (Rasheed and Hussein, 2020c). In the present study, however, we assessed the prevalence rate of S. aureus and risk factors among athletes in Zakho city, Iraq.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, usage of equipment that causes skin abrasion, and poor sanitation are also risk factors for S. aureus infection in sports (Grosset-Janin et al, 2012). Several antibiotics have been developed resistance to S. aureus in our region (Rasheed and Hussein, 2020a, Naqid et al, 2020b, Naqid et al, 2020a and methicillin-resistant S. aureus (MRSA) have also reported among hospitalized patients (Abdulkareem et al, 2020, Hussein et al, 2017, and the community (Hussein et al, 2019, Rasheed andHussein, 2020d). The prevalence of community-associated MRSA among athletes is higher particularly those people participate in direct contact sports (Rice et al, 2008), even three times greater when compared to the general community (Graham et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…PVL toxin is responsible for severe infections caused by community acquired MRSA (CA-MRSA) [15]. PVL is encoded by lukS-PV and lukF-PV genes and acts as a toxin by creating pores in leukocytes' cell membrane, leading to cell death [5,16]. We found that the prevalence of PVL-positive MRSA was (3.95%) among native Iraq, and was higher than that in Syrian refugees (2.04%).…”
Section: Discussionmentioning
confidence: 99%